Two new, brachypterous Limnellia species from the Venezuelan Andes (Diptera: Ephydridae) - Costa, Daniel N. R.; Savaris, Marcoandre; Marinoni, Luciane; Mathis, Wayne N. (Zootaxa, 2016)
Two new, brachypterous species of Limnellia are described from specimens collected in the Venezuelan Andes: L. vounitis (Trujillo: Bocon, La Cristalina (Andes; 09°14.7′N, 70°19.1′W; 2500 m)) and L. flavifrontis (Mérida: Mérida, Sierra Nevada National Park (Laguna Negra; 8°47.1’N; 70°48.4’W; 3300 m)). To facilitate identification of these unusual species, we have included a diagnosis of the tribe Scatellini and of the genus Limnellia and have also provided an annotated key to the South American genera of this tribe. The descriptions are supplemented with illustrations, photographs, and scanning electron micrographs of external structures and structures of the male terminalia.